LEGAL CONSEQUENCES OF THE REVOCATION OF LAND AND HOUSE GRANTS BY A MOTHER TO HER BIOLOGICAL CHILD UNDER THE COMPILATION OF ISLAMIC LAW - Zulaika, Emi; Ali, Moh.; Amien, Laily Firdausi Aulia (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
This study analyzed the case of grants in decision number 4301 / Pdt.G/2023 / Pa.Jr, which involves a mother who donates all of her property in the form of land and a house to one child without the consent of the other children. A grant is a voluntary transfer of property from one person to another without coercion and generally irrevocable. In this context, however, the grant is canceled because there is no consent from the other heirs who should have the same rights to the property.Revocation of a grant refers to the act of canceling the status of a grant that has previously been granted, which in this case occurs due to a violation of the procedure established in the law. Under Articles 210 and 212 of the compilation of Islamic law, grants made without the consent of all heirs are considered invalid. As a result, the deed of Grant registered in the name of the donee is considered null and void, so the grant is considered an inheritance that must be divided equally among all legal heirs, in accordance with Article 213 of the compilation of Islamic law.This study emphasizes the importance of complying with legal procedures in grants to prevent disputes. The cancellation of this grant also shows the relevance of the need for the consent of all heirs in the grant process so that it does not contradict the provisions of the applicable law.